Novel approach for detection of cell antigen coexpression using immunological biochip - A. V. Shishkin; N. G. Ovchinina; S. S. Bessmeltsev (Онкогематология, 2014)
New approach for detection of large number of different variants of cell antigen coexpression using the immunological biochip is suggested in this work. Novel construction of immunological biochip for cell investigation with test zones as strips and new special device for incubation are considered. Examples of cell analysis are given. Results are compared with data of investigation where previously known patterns of biochips were used.